Analisis Ekofeminisme De’Eaubonne terhadap Perjuangan Perempuan dalam Novel Karya Dian Purnomo - Fatimatus Zahro; Ragil Sri Wahyuningsih; Nada Vanca Anggrestia; Nuril Ahmad (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
This study examines the depiction of women’s struggles in the novel Perempuan yang Menunggu di Lorong Menuju Laut by Dian Purnomo using Françoise d’Eaubonne’s ecofeminism perspective. The novel highlights a strong connection between women and nature, both of which are subjected to oppression within a patriarchal social structure. The core issue discussed in this research is how female characters in the story respond to various forms of injustice—social, cultural, and ecological—and how the text constructs a parallel between the exploitation of women and the degradation of nature. The purpose of this study is to identify and analyze the forms of resistance expressed by the female characters against gender-based oppression and environmental damage. In addition, the research aims to demonstrate how ecofeminism serves as a critical framework to expose and challenge patriarchal dominance through literature. This research applies a descriptive qualitative method with content analysis. Data were gathered using reading and note-taking techniques, then interpreted based on De’Eaubonne’s ecofeminist theory. The results reveal that women in the novel resist domination through various actions, such as speaking out against injustice, rejecting violence, and raising environmental awareness. Their resistance is portrayed not just as personal defiance but as a collective effort rooted in ecological consciousness. The novel, therefore, becomes a medium that challenges patriarchal norms while proposing a more balanced relationship between humans and nature. In conclusion, this study affirms literature’s role as a powerful tool to voice socio-environmental concerns and promote the empowerment of women as agents of change.